Kajian Pengelolaan Lahan Terdegradasi Berbasis Agroforestri : Studi Literatur dan Implikasi untuk Restorasi Lanskap - Yadi Hartono; Wahyu Astiko (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Land degradation is a global challenge that threatens ecosystem productivity, food security, and climate resilience. Agroforestry is promoted as a multifunctional and adaptive land restoration approach to degraded landscapes. This study aims to analyze the role of agroforestry in degraded land restoration and its underlying ecological and socio-economic mechanisms. This study uses a systematic literature review with a thematic synthesis approach to reputable scientific articles and policy documents published in the period 2015-2025. The literature was selected based on the criteria of topic relevance, peer-reviewed status, and focus on the ecological and social impacts of agroforestry in the context of land restoration with a total of ±50 primary sources analyzed. The results of the study show three main findings. First, agroforestry consistently improves the quality of degraded land through improving the physical-chemical properties of soils, reducing erosion, and increasing carbon stocks. Second, the integration of agroforestry with Assisted Natural Regeneration (ANR) techniques has proven to be more effective and cost-effective in landscapes that still have natural regeneration potential. Third, the success of agroforestry is largely determined by institutional support, access to financing, and linkages to markets that strengthen the livelihoods of local communities. Based on these findings, this study recommends the integration of agroforestry-ANR in community-based restoration policies as well as the implementation of a long-term monitoring system to assess the sustainability of ecosystem services.